2014
DOI: 10.3892/or.2014.3389
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 promotes migration and invasion through mammalian target of rapamycin in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is the predominant histologic subtype of esophageal cancer and is characterized by a high mortality rate and geographic differences in incidence. microRNAs (miRNAs) are small, non-coding RNAs that play important roles in the regulation of genes associated with cancer development and progression. In the present study, we demonstrated that microRNA-100 (miR‑100) demonstrated markedly lower expression in the ESCC tissues as validated by quantitative reverse transcription-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The dual findings that miR-100 is also carried by MSC- and HSC-derived EVs [27], and that miR-100 post-transcriptionally regulates mTOR [37], led us to investigate whether it can also contribute to EV-mediated effects. First, miR-100 expression was evaluated in MCs subjected to EV treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual findings that miR-100 is also carried by MSC- and HSC-derived EVs [27], and that miR-100 post-transcriptionally regulates mTOR [37], led us to investigate whether it can also contribute to EV-mediated effects. First, miR-100 expression was evaluated in MCs subjected to EV treatment.…”
Section: Resultsmentioning
confidence: 99%
“…EVs have also been shown to display a therapeutic effect via the transfer of various miRs with protective activity [22,23,27,30]. Other potential therapeutic miRs were identified by investigating MSC and HLSC EV content, including miR-100 [27], which has been shown to target mTOR [37]. Although miR-100 content increases in HG-treated MC cells, possibly as a protective mechanism, its expression did not change upon EV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the lower expression of miR-100 in bladder cancer tissues compared to adjacent noncancerous tissues is reported to be correlated with low-grade, non-invasive bladder urothelial cancer [50,52,54]. In ESCC, miR-100 demonstrated markedly lower expression in tumor tissues than in controls as validated by quantitative reverse transcription-polymerase chain reaction [30]. Feng et al found that the expression of miR-100 in docetaxel-resistant lung adenocarcinoma cell line (SPC-A1/DTX) is significantly lower than that in parental SPC-A1 cells [35].…”
Section: Mir-100 In Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…Bhushan et al showed that miR-100 in breast cancer could target the kinasedeficient EphB6 receptor to initiate signal transduction from the cell surface to the nucleus and alter tumorigenesis and invasion [96]. Moreover, Zhang et al demonstrated that miR-100 modulated the migration and invasion of ESCC cells by targeting the mTOR 3'-UTR, and its downregulation in ESCC tissues was significantly correlated with status of lymph node metastasis in patients [30]. Argonaute 2 (AGO2), the core effector protein of the miRNAinduced silencing complex promotes tumor metastasis.…”
Section: Mir-100 In Cancer Invasion and Metastasismentioning
confidence: 99%
“…miR-645 was upregulated in human adenocarcinoma of the gastric esophageal junction and inhibited apoptosis by targeting tumor suppressor IFIT2 (11). miR-100 promoted migration and invasion through mammalian target of rapamycin in esophageal squamous cell carcinoma (12). By contrast, miR-197 was downregulated in esophageal cancer with a poor prognosis, and may play a tumor-suppressor role (13).…”
Section: Introductionmentioning
confidence: 97%